2019
DOI: 10.1002/jts.22367
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Associations Between Moral Injury and Posttraumatic Stress Disorder Symptom Clusters in Military Veterans

Abstract: War zone veterans who experience posttraumatic stress disorder (PTSD) symptoms might struggle with co‐occurring cognitive, emotional, and behavioral expressions of suffering that align with conceptual definitions of moral injury (MI). However, given that PTSD is a multidimensional condition, disentangling the apparent interplay with MI may inform clinical practice and research. This study incorporated a cross‐lagged design to explore temporal associations between self‐ and other‐directed outcomes related to MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 30 publications
4
51
1
Order By: Relevance
“…Yeterian et al, 2019), and differentiating both index events and outcomes associated with moral injury and post-traumatic stress disorder (PTSD; e.g. Jinkerson, 2016;Currier et al, 2019). Practically, questions remain regarding best practices for treating moral injury and the extent to which current treatments for PTSD are suitable to treat moral injury (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeterian et al, 2019), and differentiating both index events and outcomes associated with moral injury and post-traumatic stress disorder (PTSD; e.g. Jinkerson, 2016;Currier et al, 2019). Practically, questions remain regarding best practices for treating moral injury and the extent to which current treatments for PTSD are suitable to treat moral injury (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the precipitant, however, the outcomes appear to share many characteristics, and the two conditions have been observed to co-occur among military samples (e.g. Jordan et al, 2017;Currier et al, 2019;Davies et al, 2019). In one study, higher levels of moral injury correlated positively with "increased history of suicide attempt, but only among those higher in PTSD severity" (Bryan et al, 2018, p. 41).…”
Section: Introductionmentioning
confidence: 99%
“…Although research on morally injurious events is still in its infancy, it has been observed that not all morally injurious events meet PTSD's requirements for Criterion A traumatic events as given in the fifth edition of the DSM (i.e., DSM‐5 ; Litz & Kerig, ). Furthermore, early research suggests that although MI and PTSD are intertwined, they also appear to be distinct (Bryan, Bryan, Roberge, Leifker, & Rozek, ; Currier, McDermott, Farnsworth, & Borges, ), and that morally injurious events serve as a risk factor for a range of psychological difficulties, including suicidal ideation and behavior, depression, and substance use disorders (Battles et al., ; Bryan et al., ; Currier, Holland, & Mallot, ; Kelley et al., ; Maguen et al., ). Rather than pigeon‐holing MI to solely exist within the construct of PTSD and fear‐based biological models of posttraumatic stress, the functional contextual definition approaches MI transdiagnostically, making it applicable to a much wider range of clinical conditions.…”
Section: A Functional Contextual Definition Of Moral Injurymentioning
confidence: 99%
“…In addition to the potential impact of violations of one's moral code on functioning, MIEs have been established as a transdiagnostic risk factor for a range of psychological difficulties including posttraumatic stress disorder (PTSD), suicidal ideation and behavior, depression, and substance use (Battles et al, ; Bryan, Bryan, Roberge, Leifker, & Rosek, ; Currier, McDermott, Farnsworth, & Borges, ; Currier et al, ; Kelley, Braitman, White, & Ehlke, ; Maguen et al, ). The links between exposure to MIEs and the development of PTSD are particularly robust.…”
Section: Introductionmentioning
confidence: 99%
“…EMIS scores have been conceptualized as a proxy for moral injury. In one study, heightened moral injury as characterized by the EMIS was predictive of PTSD symptoms 6-months after initial assessment, but PTSD symptoms were not predictive of expressions of moral injury (with the exception of cluster D PTSD symptoms where the relationship was bidirectional; Currier et al, 2019). The difference between PTSD and moral injury could in part be due to the mechanisms leading to the development and maintenance of these constructs.…”
Section: Introductionmentioning
confidence: 99%